2003
DOI: 10.1557/proc-785-d11.8
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Actuators for Synthetic Jet Applications

Abstract: Synthetic jets have been identified and utilized widely in airflow control applications. These jets of air are usually created by the use of compressed air, or an electromechanically driven vibrating platform. All of these approaches produce desired results in airflow-control such as enhanced lift and increased maneuverability. Despite the results however, system weight, size, response time and force limit their use in aircraft applications where space is a premium. The objective of this study is to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…By using a two-level experimental design, velocity profiles formed at the orifice exit are used as the establishing criteria. Previous work has demonstrated that cavity height and orifice dimensions are important parameters affecting the performance of the jet (Crook et al, 1999;Baysal et al, 2004;Mossi et al, 2005;Mossi and Bryant, 2004c). Baysal et al utilized a design of experiments methodology to show that the width of the actuator cavity and the frequency of its oscillations are the most effective design variables.…”
Section: Introductionmentioning
confidence: 99%
“…By using a two-level experimental design, velocity profiles formed at the orifice exit are used as the establishing criteria. Previous work has demonstrated that cavity height and orifice dimensions are important parameters affecting the performance of the jet (Crook et al, 1999;Baysal et al, 2004;Mossi et al, 2005;Mossi and Bryant, 2004c). Baysal et al utilized a design of experiments methodology to show that the width of the actuator cavity and the frequency of its oscillations are the most effective design variables.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the brittleness of the Bimorph and the heat buildup of the RFD limited the frequency to 290 Hz and 100 Hz respectively, while the Thunder device frequency range is limited by available power [18]. Further experiments showed that a sawtooth wave input provided significantly higher jet velocities though instabilities were present [20]. Reported results showed significant velocity fluctuations with time when the actuators were driven at frequencies ranging from DC to 100 Hz.…”
Section: Introductionmentioning
confidence: 96%
“…If the oscillation of the diaphragm is sufficient in amplitude and frequency, the vortices have sufficient inertia to escape re-entrainment into the cavity resulting in an air jet consisting of propagating vortices [10]. Although the net mass change of fluid through the cavity is zero, the net momentum transferred into the fluid is non-zero [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Zero net mass flux synthetic jet actuators produce an air jet with unique effects not possible with steady suction or blowing and have the advantage of eliminating the need for plumbing connections and an internal air supply [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we study the behavior of a pre-stressed composite piezoelectric actuator 1,2 subjected to open-loop voltage and charge-feedback control. In particular, we focus on the no-load displacement behavior of a lightweight piezo-composite curved actuator (LIPCA) * .…”
Section: Introductionmentioning
confidence: 99%